2013
DOI: 10.1186/1476-511x-12-170
|View full text |Cite
|
Sign up to set email alerts
|

First-line treatment patterns and lipid target levels attainment in very high cardiovascular risk outpatients

Abstract: ObjectivesPrevious studies have demonstrated gaps in achievement of low-density lipoprotein-cholesterol (LDL-C) goals among patients at very high cardiovascular risk. We aimed to investigate lipid treatment patterns, rates and predictors of lipid targets attainment, in such outpatients in an urban area of Greece.MethodsThis was a prospective observational study, conducted in 19 outpatient clinics of Western Greece. We recruited patients with established cardiovascular disease (CVD) and/or diabetes mellitus (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…In a recent study of high or very high cardiovascular risk patients visiting a Greek university lipid treatment clinic, 95% were on any lipid-lowering treatment (LLT) and 92% were on statins, but only 25% among very high risk adult outpatients reached recommended LDL-C levels [14]. In another study involving 19 outpatient cardiology clinics in 2011–2012, it was found that, among patients with CVD or diabetes and initiating a LLT, only 25.9% received a high-efficacy regimen [15]. Thus, the question remains whether LLT in Greece is producing sufficient reductions in LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of high or very high cardiovascular risk patients visiting a Greek university lipid treatment clinic, 95% were on any lipid-lowering treatment (LLT) and 92% were on statins, but only 25% among very high risk adult outpatients reached recommended LDL-C levels [14]. In another study involving 19 outpatient cardiology clinics in 2011–2012, it was found that, among patients with CVD or diabetes and initiating a LLT, only 25.9% received a high-efficacy regimen [15]. Thus, the question remains whether LLT in Greece is producing sufficient reductions in LDL-C.…”
Section: Introductionmentioning
confidence: 99%
“…Further, cholesterol management in general has been reported to be suboptimal in high-risk patients [ 33 35 ], especially in older adults [ 33 ]. In a previous study of 396, 077 older adults (median age 75) with cardiovascular disease or diabetes in Ontario, only a small proportion were prescribed statins ( n = 75, 617 patients, 19.1%) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several potential factors may contribute to suboptimal risk factor control, including physicians' discretion to use low-potency medications as the first-line treatment, (5,39) their inertia to adjust treatment plans, (26) drug accessibility, the adverse effects of medications (27) and patients' adherence to treatment regimens. Another factor related to physicians may be adherence to older guidelines, while in patients, the fear of adverse effects from medication and lack of knowledge about the results of undertreatment may lead to poor compliance to treatment plans.…”
Section: Discussionmentioning
confidence: 99%